Makelar Kasus dalam Kajian Filosofis Normatif Hukum Islam - Abdulahanaa Abdulahanaa (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2016)
Case broker essentially reflects intervention of an administrative process of law enforcement. Thus, based the facts, case broker is already identified as an employment with proscribed income. The problem is on the one hand case broker is already connoted as a illegitimate job, on the other hand the existence of case brokers become